Outcomes of intravitreal dexamethasone implant (Ozurdex®) in patients with post-surgical macular edema – a real-world scenario - Elder Ohara de Oliveira Júnior; Isabel Ahn; Rodrigo Antonio Brant Fernandes; Arthur Gustavo Fernandes (International Journal of Retina and Vitreous)
Abstract Background Clinically significant macular edema (CME) is the leading cause of visual loss after ophthalmologic surgery due to the release of inflammatory mediators promoted by the procedures. We aimed to evaluate the outcomes of intravitreal Ozurdex® (700 µg dexamethasone) implants as a primary therapeutical option for post-surgical macular edema cases. Methods Patients with post-surgical macular edema diagnosed by optical coherence tomography (Cirrus SD-OCT) and treated with Ozudex were selected for the current study. Data was retrospectively collected from medical records from January 2020 to December 2022 and included sex, age, laterality, and timeline of treatment (i.e. implant alone or at the time of silicon oil removal in cases requiring vitreorretinal surgery). Complications associated with treatment were also noted as well as the need of further treatments. The structural analysis focused on measuring central macular thickness (CMT—average thickness within the 1 mm circle of the ETDRS) from the internal limiting membrane to the Bruch’s membrane complex, as well as the average total macular thickness including parafoveal and perifoveal regions determined by the device (CAT). The functional evaluation was based on the best-corrected visual acuity (VA) measured in logMAR. Results A total of 46 participants were included (56.2% males, mean age: 60.9 ± 11.2 years old). A statistically significant change was observed in the postoperative versus the preoperative period for all parameters (p < 0.05). The mean VA difference was − 0.17 ± 0.24; CMT was − 109.22 ± 124.85 and CAT was − 14.76 ± 58.95. We observed a significant effect of the moment of Ozurdex implantation on VA improvement, so that cases with implantation at the time of oil removal showed lower improvement than cases with implantation at a distinct timing (Coef. 0.19, 95%CI: 0.02 to 0.36, p = 0.027). Eleven cases (23.9%) required further treatment such as new Ozurdex implantation (8 cases) or surgery (3 cases). Only one case (2.17%) showed increased intraocular pressure and underwent glaucoma surgery. Conclusions Intravitreal Ozurdex implants significantly improved functional and structural aspects in post-surgical macular edema. The timing of implantation influenced VA improvement, with a distinct step approach showing better outcomes than at the time of oil removal.